Upaya Kemenkumham dalam Penanggulangan Tindak Pidana Peredaran Narkotika yang Dilakukan Petugas Lembaga Pemasyarakatan - I Nyoman Arya Mugi Raharja; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2022)
Currently, a serious problem for the Indonesian state is the circulation of narcotics. Correctional institutions are also affected by the circulation of illicit narcotics, even though the institution is an isolated place, it can be carried out by officers, therefore it needs countermeasures from the Ministry of Law and Human Rights as the ministry that oversees correctional institutions. The aims are to analyze the cause of the circulation of narcotics in Class II A Kerobokan Penitentiary and to examine the efforts of the Ministry of Law and Human Rights in following up on narcotics trafficking crimes carried out by officers of Class II-A Kerobokan Penitentiary. Empirical legal research is used in compiling this research by using a sociological approach, a statutory approach, and a conceptual approach. The sources of legal materials for this research consist of primary and secondary data. Primary data is the main data resulting from observations made during the research, this data is data from interviews with respondents. Secondary data, namely supporting data for primary data, this data is obtained through legal sources. In this research, data collection techniques use direct interviews with sources. The results show that the correctional officers committing narcotics trafficking crimes were caused by several factors such as economic factors, mental factors, environmental/social factors, and inmates who were not rehabilitated. Improving the Quality of Correctional Officers, Improving Facilities and Infrastructure, Preventing Overcrowding, Providing Appropriate and Attractive Compensation, Conducting Routine Rotation of Narcotics Dealers, Urine Testing for Correctional Officers, imposing strict sanctions on Correctional Institution officers who are found to have violated the rules in these illicit goods, in accordance with Law No. 35 of 2009 on Narcotics.